2019
DOI: 10.9734/jammr/2018/30236
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Patterns of Larynx Biopsies in Usmanu Danfodiyo University Teaching Hospital (UDUTH) Sokoto, North- Western Nigeria From 2002-2012

Abstract: Background: Laryngeal cancer is the most common of the aerodigestive tract affecting both sexes and all age groups with high morbidity and mortality when left untreated. Objectives: The study is carried out to review the histology of all larynx biopsies sent to Histopathology laboratory in UDUTH. Sokoto. Methods: A total number of forty three (43) paraffin embedded tissue block were used for the study. The blocks were retrieved from the archive and the patients' bio data and the histopathological pattern from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Similarly, the hierarchical structure associated with delay and poor accountability in provision of medical services required or expected by patients and its attendant consequences to patients avoiding hospital appointment and most of the clients cannot even afford the drugs or treatment bill (Mohammed, Aliyu & Mohammed, 2013). Accountability on the side of the hospital may continue to be a nightmare as a result of irregular implementation SERVICOM charters (Samuel, 2015;Olaopa, 2008;Ayeni, 2007).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the hierarchical structure associated with delay and poor accountability in provision of medical services required or expected by patients and its attendant consequences to patients avoiding hospital appointment and most of the clients cannot even afford the drugs or treatment bill (Mohammed, Aliyu & Mohammed, 2013). Accountability on the side of the hospital may continue to be a nightmare as a result of irregular implementation SERVICOM charters (Samuel, 2015;Olaopa, 2008;Ayeni, 2007).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…They provide the most specialized healthcare administered to patients with complex diseases that may require high risk of medical and surgical procedures with high cost technological resource (National Health Policy, 2004). It requires sophisticated medical technology, multiple specialists and subspecialists, a diagnostic support group, provision of medical consumables and medical information (Mohammed, Aliyu & Mohammed, 2013;National Health Policy, 2004). Statistics revealed that in Nigeria, 47% of the population is below 18 years while only 4% is above 60 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation